TINJAUAN FILSAFAT MANUSIA DALAM FILM DOKUMENTER INCREDIBLE MEDICAL MYSTERIES: TRANSSEXUALS - April Juwan, Dian Paula (Jurnal Filsafat "WISDOM", 2014)
Thisarticle isaresultoflibraryresearchwhichaimstounderstandtranssexual phenomenon which is a real significant problem because there is an increasing number of transsexuals who shows their existence undisguisedly as an opposite gender. The transsexual is a person who believes that psychologically he/sheÂ feels similar to the opposite gender and trapped in their biological sex. Further- more, they tend to do medical surgery on certain parts of their body to mirror the opposite gender, mostly the genital. The result of this study indicates that the transsexual is one of gender disorders which they feel 'trapped' in the wrong body. More clearly, the transsexual is a person who is physically perfect as a man or a woman but he/she has a strong tendency to express and perform him- self/herself as the opposite gender. Freedom is the highest form of perfection for the transsexual existence, but the freedom appears in their worry. Soul, accor- ding to the transsexuals, is understood as psyche. They believe that body is a re- flection of soul, and that is the reason why they undergo sexual surgery in which they want to be accepted in society as a whole human being. The trans- sexuals show their existence in order to obtain their life's purpose which is a blessed-full life as an opposite gender.